Climate change and heat stress resilient outdoor workers: findings from systematic literature review - Peymaneh Habibi; Jaleh Razmjouei; Amirhossein Moradi; Farank Mahdavi; Saeed Fallah-Aliabadi; Ahad Heydari (BMC, 2024)
Abstract Purpose Global warming has led to an increase in the number and intensity of extreme heat events, posing a significant threat to the health and safety of workers, especially those working outdoors, as they often have limited access to cooling strategies. The present systematic literature review (a) summarizes the current knowledge on the impacts of climate change on outdoor workers, (b) provides historical background on this issue, (c) explores factors that reduce and increase thermal stress resilience, (d) discusses the heat mitigation strategies, and (e) provides an overview of existing policy and legal frameworks on occupational heat exposure among outdoor workers. Materials and methods In this systematic review, we searched scientific databases including Scopus (N = 855), Web of Science (N = 828), and PubMed (N = 202). Additionally, we identified relevant studies on climate change and heat-stress control measures through Google Scholar (N = 116) using specific search terms. In total, we monitored 2001 articles pertaining to worker populations (men = 2921; women = 627) in various outdoor climate conditions across 14 countries. After full-text assessment, 55 studies were selected for inclusion, and finally, 29 eligible papers were included for data extraction. Results Failure to implement effective control strategies for outdoor workers will result in decreased resilience to thermal stress. The findings underscore a lack of awareness regarding certain adaptation strategies and interventions aimed at preventing and enhancing resilience to the impact of climate change on heat stress prevalence among workers in outdoor tropical and subtropical environments. However, attractive alternative solutions from the aspects of economic and ecological sustainability in the overall assessment of heat stress resilience can be referred to acclimatization, shading, optimized clothing properties and planned breaks. Conclusion The integration of climate change adaptation strategies into occupational health programs can enhance occupational heat resilience among outdoor workers. Conducting cost-benefit evaluations of health and safety measures for thermal stress adaptation strategies among outdoor workers is crucial for professionals and policymakers in low- and middle-income tropical and subtropical countries. In this respect, complementary measures targeting hydration, work-rest regimes, ventilated garments, self-pacing, and mechanization can be adopted to protect outdoor workers. Risk management strategies, adaptive measures, heat risk awareness, practical interventions, training programs, and protective policies should be implemented in hot-dry and hot-humid climates to boost the tolerance and resilience of outdoor workers.